Prevalence and Severity of Primary Dysmenorrhea and its Relation to Anthropometric Parameters - F Haidari; A Akrami; M Sarhadi; M Mohammad Shahi (Tehran University of Medical Sciences, 2011)
Background & Aim: Primary dysmenorrhea is a common medical disorder in young women that affects their quality of life. According to the research studies, overweight and obesity increase biosynthesis of the prostaglandin and consequently increase the severity of dysmenorrhea. The aim of this study was to examine the prevalence and severity of primary dismenorrhea and its relation to anthropometric parameters. Methods & Materials: In this descriptive-analytical study, 388 students from Ahwaz University of Medical Sciences were selected using random cluster sampling. Demographic data were collected using a questionnaire. The height and weight, BMI, fat mass, waist and hip circumferences, waist to hip ratio (WHR) and waist to height ratio (WHtR) were measured. Visual Analogue Scale (VAS) was used to evaluate the severity of dysmenorrhea. Data were analyzed using Pearson correlation test. The p<0.05 was considered to be significant. Results: Mean age of the participants was 20.7±1.8 years. The mean age at menarche was 13.4±1.2 years. Moderate or severe dysmenorrheal were experienced by 71.65% of the participants. The severity of dysmenorrhea was significantly related to body fat mass, waist circumference, hip circumference and WHtR (P<0.05). However, there was no significant relationship between the severity of dysmenorrhea with weight or BMI. Conclusion: Anthropometric parameters that are associated with central obesity such as waist circumference and WHtR are more related to the severity of dysmenorrhea. Increased visceral fat mass is a more effective predictor for dysmenorrhea. More studies are needed to clarify these relationships.